miR-34a Regulates Multidrug Resistance via Positively Modulating OAZ2 Signaling in Colon Cancer Cells - Yong Li; Ping Gong; Ji-xue Hou; Wei Huang; Xiao-ping Ma; Yu-li Wang; Jing Li; Xiao-bin Cui; Na Li (Journal of Immunology Research)
Although aberrant expression of miR-34a, an essential tumor suppressor miRNA, has been frequently observed in colon cancer (CCa), whether miR-34a can regulate CCa progression by modulating other facets of this malignancy (such as multidrug resistance, MDR) remains unknown. Here, we report for the first time that miR-34a expression was significantly downregulated in clinical CCa samples from oxaliplatin-resistant patients and in experimentally established multidrug-resistant CCa cells. By using histoculture drug response assay, we further confirmed that clinical CCa samples with lower miR-34a expression appeared to be more resistant to chemotherapy. Functionally, ectopic expression of exogenous miR-34a resensitized multidrug-resistant HCT-8/OR cells to oxaliplatin treatment, whereas miR-34a inhibition augmented the oxaliplatin resistance in chemosensitive HCT-8 cells. Mechanistically, miR-34a positively regulated the mRNA stability of the ornithine decarboxylase antizyme 2 (OAZ2) by directly targeting its three prime untranslated region (3′UTR). Consequently, suppression of the expression of miR-34a/OAZ2 signaling by chemotherapeutic agents significantly enhanced the activation of MDR-associated ATP-binding cassette (ABC) transporters and antiapoptosis pathways, thus leading to MDR development in CCa cells. Collectively, our combined analysis reveals a critical role of miR-34a/OAZ2 cascade in conferring a proper cellular response to CCa chemotherapy.